Impact of PEGylation on an antibody-loaded nanoparticle-based drug delivery system for the treatment of inflammatory bowel disease. (1st March 2022) - Shrestha, Neha; Xu, Yining; Prévost, Julien R.C.; McCartney, Fiona; Brayden, David; Frédérick, Raphaël; Beloqui, Ana; Préat, Véronique
Abstract: Nanoparticle-based oral drug delivery systems have the potential to target inflamed regions in the gastrointestinal tract by specifically accumulating at disrupted colonic epithelium. But, delivery of intact protein drugs at the targeted site is a major challenge due to the harsh gastrointestinal environment and the protective mucus layer. Biocompatible nanoparticles engineered to target the inflamed colonic tissue and efficiently penetrate the mucosal layer can provide a promising approach for orally delivering monoclonal antibodies to treat inflammatory bowel disease. The study aims to develop mucus-penetrating nanoparticles composed of poly(lactic-co-glycolic acid, PLGA) polymers with two different polyethylene glycol (PEG) chain lengths (2 kDa and 5kDa) to encapsulate monoclonal antibody against tumor necrosis factor-α (TNF-α). The impact of different PEG chain lengths on the efficacy of the nanosystems was evaluated in vitro, ex vivo, and in vivo . Both PLGA-PEG2k and PLGA-PEG5k nanoparticles successfully encapsulated the antibody and significantly reduced TNF-α secretion from activated macrophages and intestinal epithelial cells. However, only antibody-loaded PLGA-PEG2k nanoparticles were able to alleviate the experimental acute colitis in mice demonstrated by improved colon weight/length ratio, histological score, and reduced tissue-associated myeloperoxidase activity and expression of proinflammatory cytokine TNF-α levels compared with the control group. The results suggest that despite having no significant differences in the in vitro cell-based assays, PEG chain length has a significant impact on the in vivo performance of the mucus penetrating nanoparticles . Overall, PLGA-PEG2k nanoparticles were presented as a promising oral delivery system for targeted antibody delivery to treat inflammatory bowel disease. Statement of significance: There is an unmet therapeutic need for oral drug delivery systems for safe and effective antibody therapy of inflammatory bowel disease. Therefore, we have developed PEGylated PLGA-based nanoparticulate drug delivery systems for oral targeted delivery of anti-TNF-α antibody as a potential alternative treatment strategy. The PEG chain length did not affect encapsulation efficiency or interaction with mucin in vitro but resulted in differences in in vitro release profile and in vivo efficacy study. We demonstrated the superiority of anti-TNF-α mAb-PLGA-PEG2k over mAb-PLGA-PEG5k nanoparticles to effectively exhibit anti-inflammatory responses in an acute murine colitis model. These nanoparticle-based formulations may be adjusted to encapsulate other drugs that could be applied to a number of disorders at different mucosal surfaces. Graphical abstract: Image, graphical abstract